IEEE International Conference on Electric Machines and Drives, 2005. 2005
DOI: 10.1109/iemdc.2005.195948
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison between low-speed axial-flux and radial-flux permanent-magnet machines including mechanical constraints

Abstract: i -Performance comparison between different machine topologies is not a straightforward task since many variables exist if electromagnetic, thermal and mechanical aspects are taken into account. In this paper some methods to take into account relevant mechanical constraints in the performance comparison are proposed. A comparison study between low-speed axial-flux permanent-magnet machines and radial-flux permanent-magnet machines is provided with introduced mechanical constraints, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 8 publications
0
19
0
2
Order By: Relevance
“…Comparison works have been published in [6,7], proving the advantage of AF machine over radial flux machine in terms of torque density. Successful development of AFPM machine involves electromagnetic design, thermal design and mechanical design, among which, the mechanical design is most challenging because of the huge attractive force between rotor and stator disks.…”
Section: Introductionmentioning
confidence: 96%
“…Comparison works have been published in [6,7], proving the advantage of AF machine over radial flux machine in terms of torque density. Successful development of AFPM machine involves electromagnetic design, thermal design and mechanical design, among which, the mechanical design is most challenging because of the huge attractive force between rotor and stator disks.…”
Section: Introductionmentioning
confidence: 96%
“…They concluded that the axial PM structure has a reduced volume compared to the standard radial one. In [12], the authors conducted a comparison between the two topologies and found that the axial flux motor has better torque than the radial flux motor. However, in [13], the comparison between the two machines included the mechanical constraints and the cost of the active parts.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the traditional radial flux electrical machine, the axial flux electrical machine has more advantages such as the higher efficiency rotor core (more than 95%), well heat dissipation, shorter axial stator core, more compact structure, lighter weight, smaller volume, etc. To meet the need of low work speed, the more pole pairs can be designed for the axial flux electrical machine, and the bigger starting torque and higher power density [8], [9] can also be obtained. The further research and development on axial flux electrical machine are carried out by some research institutes and rich research achievements of theory and application are acquired.…”
Section: Introductionmentioning
confidence: 99%